Effect of Mg-doped CdS co-sensitization on performance of CuInSe2 quantum dot sensitized solar cells. (March 2022) - Mehmood, Ikhtisham; Shah, Abdul Hakim; Khan, Sayed Ali; Kiani, Maryam; Khan, Noor Zamin; Saeed, Aamir; Ayub, Ambreen; Khan, Fayaz; Jincheng, Huang; Muhammad, Sohail; Jiang, Le; Guijun, Li; et al.
Abstract: Metal doping can effectively enhance the photovoltaic performance of quantum dot (QD) sensitized solar cells (QDSSCs). In this study, we investigated the effect of a Mg-doped CdS (Mg–CdS) QD post-deposition layer on the optoelectronic properties of CuInSe2 (CISe) QDSSCs, which were synthesized by a low-temperature hot injection method. The ex-situ peptization technique was adopted for sensitization of CISe QDs, followed by co-sensitization of Mg–CdS through a successive ionic layer adsorption and reaction method. The fabricated TiO2 /CISe/Mg–CdS sensitized solar cell displayed excellent photovoltaic performance with a power conversion efficiency of 4.65% (Jsc = 17.43 mA/cm 2, Voc = 0.66 V) under AM 1.5 G one full-sun illumination. Furthermore, the Mg–CdS layer passivated the surface of the CISe QD solar cell, which reduced current leakage at the surface of the CISe QDs. Moreover, the Mg–CdS passivation improved stability of the solar cell. Highlights: ∙ CuInSe2 QDs and Mg–CdS deposition were carried via peptization and SILAR methods. ∙Mg doping shifts the absorption band from blue to red edge due to intraband states in CdS. ∙Mg-doping raises conduction band maxima, which increases charge transfer to TiO2 matrix.